Progress towards a leprosy-free country: The experience of Oman - Al Awaidy, Salah T. (PLOS Neglected Tropical Diseases, 2017)
Author summary Leprosy is a chronic infectious disease caused by Mycobacterium Leprae that involves many body organs but mainly skin, peripheral nerves and mucous membranes and occasionally other organ systems that affects equally all races, ages and both sexes. While most individuals exposed to an infectious case of leprosy become infected, only less than 5 percent of those infected develop the disease and subsequent disability. In Oman by World Health Organization Standard’s, Leprosy has nearly been eliminated as a public health problem over the past two decades. We are however, striving to meet the new three pillars set by WHO to achieve a completely leprosy free country. The three main strategies employed include: strengthening government ownership, coordination and partnership to stop leprosy and its complications; and to stop discrimination and promote inclusion [1–3]. We hope that through fervent efforts aim towards Oman having zero leprosy cases by WHO standards in the very near futures.